An exploration of teacher leadership: a case study in a Namibian rural primary school - Uiseb, Gerson (Rhodes University, Faculty of Education, Department of Education, 2013)
The Namibian education system has undergone a policy shift from a top-down leadership practice or head-centred leadership to a more shared form of leadership in schools. Existing policy documents call for teacher participation in school level decision-making structures and processes as teachers often are involved in other activities and have been through life experiences which equip them with leadership skills. These policies clearly stipulate that school principals cannot lead and manage the schools alone, but should involve teachers and other stakeholders in leadership activities. This study explored teacher leadership in a rural primary school in the Otjozondjupa region of Namibia. The study explored the understanding of the concept teacher leadership, the practice of teacher leadership and the enhancing factors as well as barriers to teacher leadership practice. A qualitative interpretative case study was conducted. Interviews, document analysis, focus group interviews, a questionnaire and observation were employed to produce data with regard to teacher leadership practices in the case study school. The data were analysed thematically using Grant's (2008) model of teacher leadership. Findings revealed that the concept of teacher leadership was understood as teachers leading both within and beyond the classroom. Teacher leadership was practiced across the fours zones of teacher leadership (after Grant, 2008), but to varying degrees. It could be categorized as emergent teacher leadership (after Muijs and Harris, 2005) within a formal distributed leadership framework (MacBeath, 2005). Teacher leadership in the case study school was enhanced by collaboration among staff and involvement of teachers in school level decision-making. However, barriers to teacher leadership at the case study school included holding on to power by the principal, teachers' negative attitudes towards teacher leadership, a lack of incentives, a lack of time due to a heavy work load and a lack of professional development.
Keywords: Educational leadership -- Namibia -- Otjozondjupa -- Case studies; Education, Elementary -- Namibia -- Otjozondjupa -- Case studies; School management and organization -- Namibia -- Otjozondjupa -- Case studies; Educational change -- Namibia -- Case studies; Education, Rural -- Namibia